Design of an X-band high efficiency continuous-mode power amplifier - Liu Hanxiao; Yu Zhongjun; Fan Jingxin; Zhang Desheng (Dianzi Jishu Yingyong)
To improve the bandwidth and efficiency of power amplifier, a monolithically integrated X-band high-efficiency continuous B/J power amplifier is designed based on the 0.25 μm GaAs pseudomorphic high electron mobility transistor (pHEMT) process. Continuous B/J waveform is achieved by controlling the second harmonic impedance of the output stage. The amplifier consists of two stages, with the driver stage using enhanced transistors for high gain and the output stage using depletion transistors for high efficiency and watt-level output power. The simulation results show that the power amplifier achieves an output power of 29~30.6 dBm in the frequency band of 7.3~12.2 GHz, with a power gain of 17~18.6 dB, a power added efficiency of more than 50%, a peak efficiency of 59%, an input return loss of less than 10 dB, and a chip size of only 2.1 mm × 1.3 mm.